P68 PACIFIC: a phase III, randomised, multicentre, dose escalation, efficacy and safety study examining the effects of treatment with peginterferon alfa-2a in patients with Child's A or B cirrhosis in chronic hepatitis C virus infection. (16th November 2010) - Tanwar, S; Wright, M; Foster, G; Ryder, S; Mills, P; Cramp, M; Parkes, J; Rosenberg, W
Abstract : Introduction: Trials have found conflicting results about the efficacy of pegylated interferon α (PIFN), with or without pretreatment including ribavirin, as an antifibrotic agent in patients with established cirrhosis due to persistent HCV infection. We have investigated the use of an escalating dose of PIFN2a monotherapy for 48 weeks in the treatment of patients with established cirrhosis due to persistent HCV infection. Method: A multicentre, randomised prospective controlled trial of escalating dose PIFN2a treatment of patients with HCV infection and Child's A or B cirrhosis. 39 patients were enrolled at 5 UK centres and randomised to standard clinical care, or 48 weeks treatment with PIFN2a at 90 mcg p.w. escalating each month by 45 mcg to 180 mcg p.w. if tolerated and followed for 140 weeks. Primary outcomes were liver related death; "liver related morbidity" including variceal haemorrhage, ascites and SBP, hepatocellular cancer, transplantation and all cause mortality. Secondary outcomes were health related quality of life (HRLQ). Results: There was no significant difference in the baseline characteristics between treatment and control groups (male 71:77%; mean age 55.2:52.1; Child's score 5.35:5.32; MELD 8.23:7.95). Treatment was well tolerated. 15/17 (88%) completed 48 weeks treatment; 1 at 45 mcg; 1 at 90 mcg; 2 at 135 mcg; 11 at 180 mcg. There were no differences between groups in HRQL except pain scores that were increased in the treatment group (Score=50.7:70.5, p=<0.01). Recruitment to the study was halted by the DSMC on publication of HALT-C and EPIC trial results. Conclusion: Escalating PIFN2a monotherapy is associated with HCV clearance and a reduction in liver related mortality in this small RCT. The differences from HALT-C and EPIC, and similarity to COPILOT may relate to marked differences in methodology (specifically the omission of therapy in the control arm), cirrhosis stage or sample size. These findings warrant further investigation of PIFN2a for patients with advanced cirrhosis for whom there is no other treatment and where transplantation is associated with graft infection and rapid progression to cirrhosis.